Preconception and Prenatal Smoking among Maine Women: Defining Risk and Determining the Impact of Efforts by Care Providers to Promote Cessation. (28th June 2017) - Harris, David E.; Aboueissa, AbouEl-Makarim A.; Sarton, Cheryl; Baugh, Nancy
Abstract : Introduction: Smoking before and during pregnancy is a risk for women and their babies, but encouraging tobacco abstinence challenges practitioners. Aims: We define correlates of tobacco use around pregnancy and determine the impact of providers' efforts to encourage abstinence. Methods: We analysed responses (2000 – 2010) from the Pregnancy Risk Assessment Monitoring System questionnaire for Maine, United States, a state with higher than average smoking rates. We performed multivariable logistic regression analysis with demographic and behavioural independent variables, and smoking in the last 3 months before and in the last 3 months of pregnancy as dependent variables. Results: Of 12, 409 questionnaire responders, 32% smoked before pregnancy; 60.5% of these women continued during pregnancy. Women were more likely to smoke before pregnancy and to continue during pregnancy if they had a previous birth, were unmarried, had ≤ a high school education, or had a household income ≤ $20, 000/year. Pre-pregnancy smokers were more likely to continue smoking during pregnancy if their gestational weight gain was less than recommended and, surprisingly, if they recalled a provider discussion about smoking cessation. Conclusions: We identify women at risk for smoking before and during pregnancy and demonstrate that current tobacco abstinence interventions by providers may not always be effective.